Physicochemical, Antioxidant, and Sensory Characteristics of Sponge Cake Fortified with Quinoa Flour, Oolong, and White Tea Powder - Anita Ardeshir; Fatemeh Fazeli; Nasim Khorshidian; Mehrdad Mohammadi (Journal of Food Quality)
Nowadays, there is a growing demand for healthy foods enriched with various functional bioactive ingredients. Cakes are ready-to-eat baked products consumed worldwide and are suitable for the development of functional food products. In this study, a Box–Behnken design was used to investigate the effect of three independent variables, including oolong tea powder (OT, 0–20%), white tea powder (WT, 0–15%), and quinoa flour (QF, 0–40%), on the quality characteristics of sponge cake during 21 days of storage. Following the evaluation of the model, the optimum levels of ingredients for the preparation of sponge cake were 15% WT, 17.17% OT, and 24.97% QF. Total phenolic content of 52.09 mg gallic acid/100 g, antioxidant activity of 0.068 mg/mL, overall acceptability of 4.89, lightness of 47.94, and peroxide value of 0.68 mEq/kg were obtained under optimized conditions. The growth of molds and yeasts was prevented during storage time. The hardness, gumminess, and chewiness of the optimized sponge cake improved with increasing WT, OT, and QF levels in comparison to the control. Scanning electron micrographs showed a more porous structure in optimized cake samples. In conclusion, the utilization of OT, WT, and QF as phenolic compounds in sponge cake led to an increase in its nutritional value and improved shelf life.